Differential modification of perceptual thresholds by prolonged near threshold motion in healthy adults and after peripheral lesions - Wagner, Andrew R.; Sadeghi, Soroush G.; Merfeld, Daniel M. (Frontiers in Neurology, 2025)
Purpose/hypothesisHomeostatic plasticity is an innate self-regulatory process that functions to stabilize neural excitability in response to sensory perturbations. The purpose of this study was to investigate homeostatic plasticity in vestibular perceptual responses by measuring changes in vestibular perceptual thresholds after exposure to passive whole-body self-motion stimuli (vestibular conditioning). We hypothesized that small amplitude stimuli (i.e., subthreshold conditioning) would cause a decrease in thresholds, whereas large amplitude stimuli (i.e., suprathreshold conditioning) would cause an increase in thresholds.MethodsOne-Hz yaw rotation vestibular perceptual thresholds were measured before and immediately after 20-min blocks of passive whole-body motion (i.e., conditioning) in a cohort of 12 healthy adults (27 ± 8.19 years; 10 female). The conditioning stimuli consisted of 1 Hz sinusoidal motions and included (a) subthreshold yaw rotations with a peak velocity equal to 57.4% of the baseline threshold (T0.57x), (b) suprathreshold yaw rotations with a peak velocity equal to 200% of the baseline threshold (T2x), or (c) a sham stimulus consisting of 0.1 mm/s interaural translations (TSham). A subset of the group returned to complete an additional subthreshold yaw rotation condition with a peak velocity equal to 20% of the baseline threshold (T0.2x). A cohort of 5 individuals (1 female) with chronic unilateral vestibular hypofunction participated in the T0.57x subthreshold conditioning stimulus.ResultsYaw rotation thresholds were significantly increased after suprathreshold conditioning (1.36 ± 0.75°/s, p = 0.004), increasing an average of 31.75% relative to baseline (1.05 ± 0.52°/s). However, counter to our hypothesis, yaw rotation thresholds were not significantly lowered in our healthy adult population after either of the two subthreshold conditioning tasks (T0.57x: 1.11 ± 0.62°/s, p = 0.61; T0.2x: 1.20 ± 0.69°/s, p = 0.385). Yet, four out of the five participants with chronic unilateral vestibular hypofunction displayed an improvement in perceptual thresholds (Range of 10.32–29.14%) following the T0.57x subthreshold conditioning task.ConclusionThese data suggest (1) that 20 min periods of passive whole-body motion are sufficient to modify vestibular perception and (2) that the impact of subthreshold conditioning on perceptual thresholds may depend on the baseline integrity of the vestibular system.